Salat Dhuha Improves Blood Pressure: A Randomized Controlled Trial - Boy, Elman; Lelo, Aznan; Tarigan, Amira Permatasari; Machrina, Yetty; Yusni, Yusni; Harahap, Juliandi; Sembiring, Rosita Juwita; Syafril, Santi; Sumartiningsih, Sri (Media Ilmu Keolahragaan Indonesia, 2021)
The prevalence of hypertension increases with age, more than 1 in every two elderly has hypertension, dominated by women. The primary prevention of hypertension is a worldwide public health concern. Salat dhuha is a moderate-intensity physical activity. Salat 2 movement cycles demonstrated improved systolic and diastolic blood pressure in adults. Our study purpose was to assess the effect of 2 and 8 movement cycles (rakaat) of salat dhuha to improve systolic and diastolic blood pressure in healthy Muslim elderly women. Muslim elderly women in a government senior residence (aged 60-74 years) participated in a 6 weeks controlled trial. We completed formal physical, clinical, and blood assessments before admission. Participants with hypertension history were excluded. The participants were randomized into 2 groups. The intervention group performed 8 rakaat of salat dhuha (n=13) and the control group performed 2 rakaat of salat dhuha (n=13). Two participants were dropped out of this study. At baseline and at the end of 6 weeks, a blood pressure examination is recorded. Parametric and nonparametric methods were used to analyze the data. The baseline characteristics of the two groups of participants were homogeneous. Compared to the control, the 8 rakaat of salat dhuha achieved a significant reduction in systolic and diastolic blood pressure (P0.05) at the end of the 6-weeks period. The findings show that salat dhuha has significant potential to improve blood pressure.